Nurturing pioneering minds towards innovation-based economy: Leveraging the Innovative performance on human capital through social embeddedness and pro- innovativeness organisationc11 architecture. - Abdul Halim, Hasliza (Pusat Pengajian Pengurusan, 2014)
Malaysia needs a paradigm shift from a knowledge-based economy to innovation-centred in order to stand in the same row with advanced nations. As propagated in the New Economic Model Agenda, according to Prime Minister Datuk Seri Najib Tun Razak, moving towards this economy is crucial especially in efforts to integrate the economy with the global economic network. Malaysia needs to continue to bring changes to the economy in order to move towards innovationcentred economy.The three main features are creativity, innovation value and high skills.